Cloud-based Master Data Management: Transforming Enterprise Data Strategy - Chandra Sekhara Reddy Adapa, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud-based Master Data Management (MDM) solutions are revolutionizing how organizations handle critical data assets in today's rapidly evolving digital landscape. These solutions offer enhanced scalability, flexibility, and real-time access capabilities that traditional on-premises systems struggle to match. By leveraging advanced technologies such as artificial intelligence, machine learning, and microservices architecture, cloud-based MDM enables organizations to achieve superior data quality, improved operational efficiency, and better business outcomes. The integration of blockchain technology and IoT capabilities is further transforming how enterprises maintain data integrity and manage connected device information. Modern MDM platforms incorporate comprehensive security frameworks and intelligent data management features, allowing organizations to maintain robust governance while adapting to changing business requirements. Through API-led connectivity and microservices architecture, these solutions provide enhanced integration capabilities and architectural flexibility. The advancement of cloud-native architectures, combined with AI-driven automation and analytics, positions cloud-based MDM as a crucial enabler of digital transformation and business success.
Keywords: Cloud-based Master Data Management; Enterprise Data Strategy; Data Governance; Digital Transformation; Artificial Intelligence Integration